Assessment of Calamus tenuis fruits extract on blood glucose level elevation and its antibacterial potency - Sarkar, Hema; Sharin, Tasfia; Mamun, Muhammad Shamim Al (Journal of Applied Pharmaceutical Research, 2018)
Investigation of anti-hyperglycemic and antibacterial activity of the fruit extract of Calamus tenuis was carried out. Soxhlet extraction was done using petroleum ether, ethyl acetate and methanol. Anti-hyperglycemic activity was done by Oral Glucose Tolerance Test. The results indicated that methanol extract showed nearly same potency of blood glucose lowering capacity with a dose of 500 mg/Kg (4.82 ± 0.730 mmol/L) compared to the glibenclamide (standard drug) produced (4.26 ± 0.441 mmol/L) at 5 mg/Kg dose after 120 min of glucose feeding to mice. Antibacterial activity was investigated using disc diffusion method. Antibacterial tests revealed that S. aureus was resistant to all the solvent extracts. Ethyl acetate and methanol extracts showed moderate antibacterial capacity against both Micrococcus and V. cholerea whereas petroleum ether showed nothing. Zone of inhibition of Ethyl acetate and methanol extracts (200 mg/mL dose) for E. coli were very close to positive control (17.00 ± 0.816 and 18.75 ± 1.258 mm respectively; positive control value was 19.00 ± 1.414 and 21.00  ± 1.414 respectively ). In case of methanol zone of inhibitions were greater than other solvent extracts against all tested bacterial species. From this study it can be concluded that the C. tenuis fruit may serve as a new potential source of medicines due to the presence of biological activity.